Analysis of factors influencing student motivation in entrepreneurship at the faculty of education UNNES - Kriswanto, Hendra Dedi; Hasjiandito, Akaat; Swaraswati, Yogi; Widianto, Wawan (AIP conference proceedings, 2024)
The study, "Analysis of Factors Influencing Students’ Entrepreneurial Motivation in the Faculty of Education at Universitas Negeri Semarang," underscores the importance of identifying and analyzing factors that drive student entrepreneurship. The parameters examined encompass social environment (x1), education (x2), and work experience (x3). The subjects of this research were students at the Faculty of Education and Psychology, Universitas Negeri Semarang, while the number of respondents in this research was 149. This research aims to probe these variables’ impact on students’ entrepreneurial enthusiasm. The methodology employed was a survey and questionnaire dissemination to a select pool of students at the Faculty of Education, Universitas Negeri Semarang. Research outcomes evidence that social setting significantly impacts entrepreneurial drive. Greater entrepreneurial zeal was observed when the immediate environment was supportive and provided thriving examples of entrepreneurship. The educational framework had an analogous effect. A propitious curriculum and entrepreneurial training heightened student drive. In addition, work experience played a critical role, with experienced students showcasing elevated entrepreneurial drive given their prior business management insights and skills. The findings conclude that entrepreneurial drive can be nurtured through a supportive social ambiance, a conducive educational curriculum, and early exposure to work experiences. Universities should leverage this insight by offering more entrepreneurship programs or training to impart students with practical knowledge and talent in this discipline.